The economy of Rome in the communal period (1143-1398): a numismatic perspective - Valci, Mariele (2019)
Between 1143 and 1398, Rome was a city of merchants involved in national and international trade, ruled by two different authorities – the Roman Senate and the pope – which constantly referred to the City’s glorious past in order to legitimise their power. From the late tenth century until c.1184, Rome did not have a mint. Instead, it used foreign coins to maintain a monetized economy. A few important recent studies have drawn attention to this period, focusing mostly on Rome’s socio-political profile. Crucially, however, none of these has systematically exploited the data of material evidence. This research project aims to fill this gap, examining the Rome commune from an archaeological perspective with a specific focus on the available numismatic sources. The analysis of this rather neglected material is shown to be crucial for understanding diverse aspects of Rome’s economic, political and social profile, for example, the processes through which foreign money reached the city; the reasons behind the reopening of Rome’s mint in c.1186; the changing balance of power between the Roman Senate and the pope during the commune; and the multiple roles played by coinage in Rome’s medieval society. This project focuses on the systematic examination of 5809 coins preserved in the coin cabinets of three of Rome’s major museums – Museo Nazionale Romano, Musei Capitolini and Biblioteca Apostolica Vaticana – and in the Department of Coins and Medals at The British Museum in London, and through the analysis of 26 finds recovered in excavations in the Colosseum and at the site of Tuscolo (c.30 km south-east of Rome). The study of the archaeological evidence is supported by examination of 678 archival documents, which comprise 160 acts of diverse monasteries, and 588 notarial acts compiled between 1347 and 1398. Through these combined analyses, this thesis discusses the main actors contributing to the introduction of foreign coins into Italy between the tenth and twelfth centuries, the reasons behind the reopening of Rome’s mint in c.1186, the changes made to the denaro provisino – the most popular coin minted by the city throughout the communal period – and the multiple functions served by this issue as a means of exchange, a measure of account, an offering in ritual depositions, a means of saving and as a vehicle for political messages. The study thus gives important new angles to reconstructing the economy and powers of communal Rome.